Driving style recognition for intelligent vehicle control and advanced driver assistance: a survey - Marina Martinez, Clara; Heucke, Mira; Wang, Fei-Yue; Gao, Bo; Cao, Dongpu (IEEE, 2017)
Driver driving style plays an important role in vehicle energy management as well as driving safety. Furthermore, it is key for advance driver assistance systems development, toward increasing levels of vehicle automation. This fact has motivated numerous research and development efforts on driving style identification and classification. This paper provides a survey on driving style characterization and recognition revising a variety of algorithms, with particular emphasis on machine learning approaches based on current and future trends. Applications of driving style recognition to intelligent vehicle controls are also briefly discussed, including experts' predictions of the future development.
Keywords: Driving style; Driving conditions; Driver behavior; Driving style recognition; Machine learning; Intelligent vehicle control; Energy efficiency; Driving safety